ISO 9000-Concept and Implementation in a Service Sector - Jain, Samir Kumar; Agrawal, Rishi (Journal of Engineering Education Transformations, 1993)
Till recently the approach in industry was towards appraisal and correction of quality which can be called as quality through inspection. The same is now getting changed as Quality Assurance Approach. ISO 9000 is an international series of standards which intends to achieve the same. They are also known as contractuals standards. Any organisation who is in the field of supplying products and services and comprising of 10 to 10,000 people can adopt the standard. These standards are advantageous as they inspire the customers, reduce multiplicity of inspection, improves efficiency, reduces wastage improves potential of exporting, provides systematic working environment etc. In this paper an attempt has been made to lay more emphasis on the implementation of ISO 9001 in service organisation, its requirement and mandatory documents required for its implementation. In India, many purely service sector organisations are implementing these standards. Certification mayor may not be required, but definitely the concept of quality assurance systems can be effectively used for improved "customer satisfaction" in the service sector also.